Muscle activation differences during eccentric hamstring exercises - Guruhan, S.; Kafa, N.; Ecemis, Z. B.; Guzel, N. A. (Sports Health: A Multidisciplinary Approach, 2021)
Background: The hamstring muscles play a critical role in the prevention of lower limb injuries. However, it is still unclear which exercises are more effective in terms of muscle activation. Hypothesis: In healthy individuals, there are differences between muscular activations of the biceps femoris (BF), semitendinosus (ST), and semimembranosus (SM) muscles during eccentric hamstring exercises. Study Design: Cross-sectional. Level of Evidence: Level 2. Methods: A total of 31 healthy participants (18 male; mean age, 22.5 years; SD, 3.1) were included in this study. The maximum voluntary isometric contraction of the hamstring muscles was measured using an isokinetic dynamometer. The participants were asked to perform one of the following exercises randomly (3 repetitions each): stiff-leg deadlift (SLDL), unilateral stiff-leg deadlift (USLDL), Nordic hamstring exercise (NHE), and ball leg curl (BLC). Activation of the BF, ST, and SM muscles was measured using surface electromyography during the exercises. In the statistical analysis of this study, factorial analysis of variance was used to compare the effects of each exercise on the muscle groups and to analyze which exercise type was more effective for each muscle group. Results: The NHE led to higher muscle activation than the other exercises (P < 0.001). When exercise type and muscle interaction were examined, SM activation was lower than BF (P = 0.04) and ST (P = 0.001) during NHE (P < 0.05). The highest level of muscular activation was recorded during the NHE in both male and female participants. Conclusion: The NHE may be the most effective exercise for the hamstring muscles as it leads to greater muscle activation. SLDL, USLDL, and BLC exercises may be preferred at the beginning of strength training programs since they lead to lower muscular activation compared with the NHE. Clinical Relevance: To select the optimum hamstring exercise, it is important to know the activation levels of the hamstring muscles during different eccentric exercises.